TEACHING SPEAKING BY USING SHORT CARTOON MOVIES TO SENIOR HIGH SCHOOL STUDENTS - Fitrona Hadryanti; Don Narius (Universitas Negeri Padang, 2016)
Speaking ability is very important in English learning to make it easier for someone to exchange information or ideas with others. However, there are still many high school students having problems in speaking. Therefore, the teachers’ teaching techniques should consider increasing students’ motivation, confidence and maximizing speaking activities in the classroom. The use of short cartoon movies is one of the teaching techniques to help teachers tackle the problems. In this technique, students will watch a short cartoon movie based on the topics to be studied. After discussing the events in the movie, the teacher will lead students to be able retelling the movie in pairs in front of the class. By using this technique, students can increase their confidence to speak, reduce boredom due to the use of interesting media and also to improve their behavior through moral values in the story.